ADVANCING THE DIFFERENTIAL DIAGNOSIS OF HSIL AND LSIL IN PERIMENOPAUSE: A REVIEW OF MODERN OBJECTIVE CRITERIA - Reymnazarova Gulsara Djamalovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Cervical cancer remains a significant global health burden, ranking as the fourth most common malignancy among women worldwide, with approximately 660,000 new cases and 350,000 deaths reported in 2022. Despite advances in vaccination and screening, the disease disproportionately affects low- and middle-income countries, where incidence and mortality rates remain alarmingly high. Persistent infection with high-risk human papillomavirus (HPV) types, predominantly HPV 16 and 18, drives cervical carcinogenesis through the oncogenic actions of E6 and E7 proteins, which inactivate tumor suppressors p53 and pRb. The premenopausal period represents a particularly vulnerable window, during which hormonal fluctuations, immunological changes, and increased HPV susceptibility converge to elevate the risk of cervical intraepithelial neoplasia progression. This review synthesizes recent evidence on innovative diagnostic approaches for precancerous cervical lesions, with emphasis on integrated morphological, immunohistochemical, and nanoscale analytical methods. We examine the diagnostic utility of dual p16/Ki-67 immunostaining as a triage strategy for HPV-positive women, highlighting its superior sensitivity and specificity compared to conventional cytology. Emerging technologies including atomic force microscopy, scanning electron microscopy, and elemental tissue analysis are discussed as complementary tools for characterizing the biophysical and biochemical landscape of cervical dysplasia. The review further considers the role of DNA methylation markers, artificial intelligence-assisted diagnostics, and the incorporation of these modalities into risk stratification algorithms. Special attention is devoted to the clinical implications of these innovations for women in the premenopausal age group, where early detection and individualized management are critical for cancer prevention and fertility preservation.